Znaczenie semestralnego rozkładu zajęć w prawidłowym żywieniu studentów = The importance of semester timetable in correct student's nutrition - Ewelina Kozłowska; Anna Kowalczyk; Eliza Wołoszynek; Olga Dąbska; Urszula Bojakowska; Paweł Kalinowski; Danuta Podstawka; Marta Makara-Studzińska (Kazimierz Wielki University, 2016)
Kozłowska Ewelina, Kowalczyk Anna, Wołoszynek Eliza, Dąbska Olga, Bojakowska Urszula, Kalinowski Paweł, Podstawka Danuta, Makara-Studzińska Marta. Znaczenie semestralnego rozkładu zajęć w prawidłowym żywieniu studentów = The importance of semester timetable in correct student's nutrition. Journal of Education, Health and Sport. 2016;6(8):305-315. eISSN 2391-8306. DOI http://dx.doi.org/10.6084/m9.figshare.3749112 http://ojs.ukw.edu.pl/index.php/johs/article/view/3761 https://pbn.nauka.gov.pl/sedno-webapp/works/743686     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016.     Znaczenie semestralnego rozkładu zajęć w prawidłowym żywieniu studentów   The importance of semester timetable in correct student's nutrition     Ewelina Kozłowska1, Anna Kowalczyk2, Eliza Wołoszynek2, Olga Dąbska3, Urszula Bojakowska1, Paweł Kalinowski1, Danuta Podstawka4, Marta Makara-Studzińska4     1Samodzielna Pracownia Epidemiologii, Uniwersytet Medyczny w Lublinie 2Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3Zakład Patologii i Rehabilitacji Mowy, Uniwersytet Medyczny w Lublinie 4Zakład Psychologii Stosowanej, Uniwersytet Medyczny w Lublinie       Słowa kluczowe: żywienie, studenci, rozkład zajęć. Keywords: nutrition, students, timetable.   Streszczenie Wprowadzenie i cel pracy: Grupą społeczną szczególnie narażoną na uleganie antyzdrowotnym zachowaniom żywieniowym są studenci, których dzień zdeterminowany jest narzuconym przez uczelnię semestralnym planem zajęć. Celem podjętych badań było określenie wpływu satysfakcji z semestralnego rozkładu zajęć na sposób żywienia młodzieży akademickiej. Materiał i metoda:  Badanie przeprowadzono wśród stu wybranych studentów Uniwersytetu Medycznego w Lublinie posługując się autorskim kwestionariuszem ankiety. Analizę statystyczną wykonano nieparametrycznym testem statystycznym χ2 Pearsona. Wyniki: 70% studentów  jest  niezadowolonych z obecnego planu zajęć, biorąc pod uwagę możliwość zdrowego odżywiania się. Najliczniejszą grupę studentów oceniających plan zajęć jako dostosowany do ich potrzeb żywieniowych stanowią osoby mieszkające w akademikach. Stwierdzono istotną statystycznie zależność między niezadowoleniem z planu zajęć, a brakiem czasu na samodzielne przygotowanie pełnowartościowych posiłków (p=0,000653). Plan zajęć nie wpływa istotnie na częstotliwość pojadania między posiłkami, jednakże studenci niezadowoleni z niego częściej jedzą w pośpiechu. Wnioski: Młodzież akademicka napotyka na utrudnienia w stosowaniu zaleceń zdrowego odżywiania, które wynikają bezpośrednio z nieodpowiadającego im planu zajęć. Osoby odpowiedzialne za  tworzenie rozkładów zajęć w trosce o zdrowie studentów powinni mieć na uwadze ich potrzeby żywieniowe.     Abstract Introduction and work aim: Social group particularly exposed to anti-health nutritional behaviour are students, whose day is determined by the University imposed semester timetable. An aim of the study was to define the impact of satisfaction from a semester timetable on nutrition of the university students. Material and Method: The study was conducted among one hundred randomly chosen students of Medical University in Lublin using the author's questionnaire form. Statistical analysis was carried out with nonparametric Pearson's χ2 statistical test. Results: 70% of students are dissatisfied with current schedule, taking into account the possibility of healthy nutrition. The largest group of students assessing their timetable as adapted to their dietary needs constitute persons staying in hostels. A statistically significant relation between dissatisfaction with timetable, and the lack of time to prepare nutritious meals was stated (p = 0.000653). Timetable doesn't affect on frequency of snacking between meals; however students dissatisfied with it more often eat in a hurry. Conclusions: University students come across difficulties in application of healthy nutrition recommendations resulting directly from not-suited timetable. Persons responsible for creation of timetables with concern for health of students should take into account their dietary needs.